Is the Non-Justiciability of Economic and Socio-Cultural Rights in the Nigerian constitution Unassailable? Re-Examining Judicial Bypass from the Lens of South African and Indian Experiences - Hemen Philip Faga; Francis Aloh; Uchechukwu Uguru (Universitas Lampung, 2020)
The 1999 Constitution of the Federal Republic of Nigeria, as amended (CFRN) recognizes the entitlement of every Nigerian within its borders to enjoy economic and socio-cultural (ESC) rights under Fundamental Objectives and Directive Principles of State Policy. However, the constitution seemingly renders these ESC rights non-justiciable or unenforceable. This paper examines the efforts of the Nigerian judiciary to bypass the non-Justiciability provision to enforce ESC rights in Nigeria. It mainly investigates the role of judicial decisions in other similar jurisdictions such as South Africa and India in shaping the jurisprudence of the enforcement of ESC rights in Nigeria. Therefore, the paper adopts the comparative method and recommends that both the Nigerian legislature and the judiciary should follow the example of enforcement of ESC rights in these other jurisdictions.